2000
DOI: 10.2337/diabetes.49.6.975
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion and insulin sensitivity in relation to glucose tolerance: lessons from the Botnia Study.

Abstract: Recently, a new stage in glucose tolerance, impaired fasting glucose (IFG) (fasting plasma glucose level of 6.1-6.9 mmol/l), was introduced in addition to impaired glucose tolerance (IGT) (2-h glucose level of 7.8-11.0 mmol/l). It is not clear whether IFG and IGT differ with respect to insulin secretion or sensitivity. To address this question, we estimated insulin secretion (by measuring both insulin levels and the ratio of insulin-toglucose levels in 30-min intervals) and insulin sensitivity (by using the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
236
7
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(273 citation statements)
references
References 41 publications
22
236
7
8
Order By: Relevance
“…Our results are consistent with other studies performed in other populations, which found that an increase in insulin resistance is the principal defect observed in subjects with IFG, while impairment in beta-cell function is the major pathology that leads to the development of IGT [8][9][10][11]. However, some other studies found opposite results [12][13][14].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with other studies performed in other populations, which found that an increase in insulin resistance is the principal defect observed in subjects with IFG, while impairment in beta-cell function is the major pathology that leads to the development of IGT [8][9][10][11]. However, some other studies found opposite results [12][13][14].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, subjects with isolated IFG and combined glucose tolerance (CGT) manifested higher frequency of lipid disturbances, which are associated with increased insulin resistance [24], and therefore had a higher frequency of the metabolic syndrome compared to subjects with NGT and IGT. Normal subjects in this population had normal fasting and 2-h glucose concentrations and their HOMA-IR values were relatively greater than NGT subjects in other populations [10,12]. Higher BMI (31 in this study compared to [25][26][27] in the other studies) may explain the large HOMA-IR value in this population.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In a study of Pima Indians, participants with isolated IFG and isolated IGT showed similar impairments in insulin sensitivity, but those with isolated IFG had a more pronounced defect in early insulin release and higher endogenous glucose output [10]. Tripathy et al [11], on the other hand, concluded that IFG was characterised by insulin resistance, whereas persons with IGT had impaired insulin secretion. Similar findings were reported by Hanefeld et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have given conflicting data on the association of IFG and IGT with insulin resistance and impaired insulin secretion [10][11][12][13][14][15][16][17][18][19][20]. In a study of Pima Indians, participants with isolated IFG and isolated IGT showed similar impairments in insulin sensitivity, but those with isolated IFG had a more pronounced defect in early insulin release and higher endogenous glucose output [10].…”
Section: Introductionmentioning
confidence: 99%